1989
DOI: 10.1159/000215979
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of Deep Venous Thrombosis with a Low-Molecular-Weight Heparin (Kabi 2165/Fragmin®) in Stroke Patients

Abstract: In a group of 60 patients in the acute phase of an ischemic stroke the assumption that low-molecular-weight heparin Kabi 2165 in the dose of 2 × 2,500 anti-Xa units s.c. could prevent thromboembolic complications was tested using a double-blind, placebo-controlled, randomized trial design. Thirty patients were allocated to each group. Both treatment groups were comparable with regard to neurological status and general condition. In the Kabi 2165 group there were 6 cases of deep venous thrombosis (DVT) compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 15 publications
0
39
0
1
Order By: Relevance
“…After scanning titles and abstracts, 743 citations were excluded and 23 were retained for further evaluation. Eighteen studies were excluded for the following reasons: data on cardioembolic strokes were not reported in 9 trials 8 -16 ; one trial did not have a control group 17 ; 2 trials were nonrandomized 18,19 ; randomization was performed after 48 hours from onset in 2 trials 20,21 ; cardioembolic strokes were excluded in 3 trials [22][23][24] ; and no computed tomography scan before randomization was performed in one trial. 25 Two studies were reincluded in the analysis because the authors provided us with data on cardioembolic strokes not previously reported in the original published articles.…”
Section: Study Selectionmentioning
confidence: 99%
“…After scanning titles and abstracts, 743 citations were excluded and 23 were retained for further evaluation. Eighteen studies were excluded for the following reasons: data on cardioembolic strokes were not reported in 9 trials 8 -16 ; one trial did not have a control group 17 ; 2 trials were nonrandomized 18,19 ; randomization was performed after 48 hours from onset in 2 trials 20,21 ; cardioembolic strokes were excluded in 3 trials [22][23][24] ; and no computed tomography scan before randomization was performed in one trial. 25 Two studies were reincluded in the analysis because the authors provided us with data on cardioembolic strokes not previously reported in the original published articles.…”
Section: Study Selectionmentioning
confidence: 99%
“…Но если взглянуть на абсолютные цифры, зарегистрированные в опыт ных группах на фоне применения изучаемых мето дик, то они могут варьировать в широких пределах, подчеркивая гетерогенность выборки, а их среднее значение далеко от идеального уровня. Так, у лиц с острым нарушением мозгового кровообращения, сопровождающимся парезами и параличами ниж них конечностей, частота верификации ВТ на фоне стандартной профилактики, включающей эластич ную компрессию, интермиттирующую пневмоком прессию, прямые антикоагулянты, находится в ин тервале 4-23% со средним значением 11,6% [17][18][19][20][21][22][23][24][25]. При хирургическом лечении онкологических заболеваний частота развития ВТ составляет 6,25-55,5% (в среднем 15,9%) на фоне применения анти коагулянтов и компрессионной терапии [26][27][28][29][30][31][32][33][34][35][36].…”
Section: флебология 1 2015unclassified
“…The rate of discovering a deep venous thrombosis (DVT) is also directly dependent on the screening test used and on whether the test was obtained based on clinical suspicion or not. For example, using I 125 fibrinogen scanning, the rate of DVT ranges from 30 to 80%, to as low as 5% using Doppler ultrasound [14,15]. Even in patients who were treated with thomboprophylaxis, the incidence of VTE can be significant.…”
Section: Prophylaxis For Venous Thromboembolismmentioning
confidence: 99%